2019
DOI: 10.1111/hae.13730
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of patients with haemophilia in Brazil: First report

Abstract: Introduction Brazil has the fourth largest world population of patients with haemophilia. However, mortality rates in this population are unknown. Aim To analyse mortality and its causes in Brazilian patients with haemophilia from 2000 to 2014. Methods The number of deceased patients with haemophilia and causes of death were obtained from the Brazilian National Mortality Information System (SIM), according to the 10th International Classification of Diseases (ICD‐10). Standardized mortality ratios (SMR) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(77 citation statements)
references
References 18 publications
1
70
0
6
Order By: Relevance
“…The global incidence of cardiovascular‐related deaths in the general population is high; 23,24 in the United States in 2017, “diseases of the heart” accounted for 23.3% of total deaths and “cerebrovascular diseases” (ie, stroke) accounted for a further 5.0% of the total deaths 23,53 . Studies reporting the proportion of deaths due to CVD in PwcHA range from 4% 54 to 25.5%, 55 although a number of studies suggest that this risk may be lower than in the general population 54‐58 . However, determining the association between cardiovascular mortality and HA is complicated by the fact that cardiovascular risks overlap between HA‐associated and non‐HA‐associated mortality causes (Figure 1); and there is conflicting evidence on the level of cardiovascular (including thrombotic) risk in PwcHA relative to the general population 58,59 .…”
Section: Resultsmentioning
confidence: 99%
“…The global incidence of cardiovascular‐related deaths in the general population is high; 23,24 in the United States in 2017, “diseases of the heart” accounted for 23.3% of total deaths and “cerebrovascular diseases” (ie, stroke) accounted for a further 5.0% of the total deaths 23,53 . Studies reporting the proportion of deaths due to CVD in PwcHA range from 4% 54 to 25.5%, 55 although a number of studies suggest that this risk may be lower than in the general population 54‐58 . However, determining the association between cardiovascular mortality and HA is complicated by the fact that cardiovascular risks overlap between HA‐associated and non‐HA‐associated mortality causes (Figure 1); and there is conflicting evidence on the level of cardiovascular (including thrombotic) risk in PwcHA relative to the general population 58,59 .…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of death by cardiovascular disease and cancer was less frequent in the haemophilia cohort compared with the general male population. This has previously been confirmed by Kamphuisen et al, 27 and more recently, Jardim et al, 20 Lövdahl et al 28 and Payne et al 29…”
Section: Discussionmentioning
confidence: 99%
“…Severe haemorrhage, including ICH, remains an important cause of death in PWH 19,20 . However, the remarkable advances in haemophilia treatment, and thus, the prolonged life expectancy, have resulted in more “common” diseases and causes of death, such as malignancies and age‐related cardiovascular death 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…The main causes of death are bleeding and hepatitis‐ and HIV‐related diseases . As intracranial hemorrhage is a major cause of fatal bleeding in nonsevere hemophilia, this remains an important concern for hemophilia caregivers . The INSIGHT study demonstrated that intracranial hemorrhage was the cause of death in 12% of the 148 patients with nonsevere hemophilia A who died during an observation period of 30 years.…”
Section: Life Expectancy and Quality Of Lifementioning
confidence: 99%